2023
DOI: 10.1371/journal.pone.0286213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the appearance of osteochondrosis lesions by two radiographic examinations in sport horses aged from 12 to 36 months

Abstract: Osteochondrosis is a developmental orthopedic disease characterized by a defect of enchondral ossification. This pathological condition develops and evolves during growth and is influenced by various factors, in particular genetic and environmental. However, little research has been conducted on the dynamic of this condition in horses after the age of 12 months. The retrospective study presented here investigates changes in osteochondrosis lesions through two standardized radiographic examinations carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In the stifle, osteochondrosis of the midregion of the lateral femoral trochlea can resolve in the first 8 months of life [ 35 ]. In a radiographic study, osteochondrosis lesions of the third metacarpal bone appeared, disappeared or evolved between the age of 12 and 36 months in Warmblood sports horses [ 36 ]. This is in agreement with our study which demonstrated that osteochondrosis lesions of the sagittal ridge of the third metacarpal bone have the potential to resolve even in two-year-old Thoroughbreds.…”
Section: Discussionmentioning
confidence: 99%
“…In the stifle, osteochondrosis of the midregion of the lateral femoral trochlea can resolve in the first 8 months of life [ 35 ]. In a radiographic study, osteochondrosis lesions of the third metacarpal bone appeared, disappeared or evolved between the age of 12 and 36 months in Warmblood sports horses [ 36 ]. This is in agreement with our study which demonstrated that osteochondrosis lesions of the sagittal ridge of the third metacarpal bone have the potential to resolve even in two-year-old Thoroughbreds.…”
Section: Discussionmentioning
confidence: 99%